Investigation of the Potential Environmental Risks of Phthalate Derivatives Designed To Be Environmentally Friendly. (26th April 2020) - Zhang, Wenhui; Sun, Ruihao; Hou, Yilin; Qiu, Youli; Li, Yu
Abstract: Phthalate derivatives with low estrogenic activity, high infrared spectrum signals, high Raman characteristic vibration spectrum, high fluorescence intensity, and high ultraviolet sensitivity were selected as precursors from our previous studies, so that the changes in their toxicity and estrogenic activity during biological metabolism, ozone oxidation, photocatalytic degradation, photodegradation, and microbial degradation could be studied.The transformation pathways of these derivatives were simulated, and the reaction energy barriers were calculated. To determine the potential environmental risks of these phthalate derivatives, the pharmacophore models of biotoxicity and estrogen activity of phthalates were used to predict the biotoxicity and estrogen activity of the transformed products. The results showed an increase in the biotoxicity and estrogen activity of the biometabolites, ozonation products, photocatalytic degradation products, and microbial degradation products; the only products that did not follow this trend were the photodegradation products. Notably, the pathways that produced more potentially toxic compounds were the less favorable paths. Our results indicate that the transformation products of the designed environmentally friendly phthalate derivatives potentially pose environmental risks. To avoid such risks, the environmental transformation pathway of these derivatives should be simulated to screen for environmentally friendly phthalate molecules. Environ Toxicol Chem 2020;39:1138–1148. © 2020 SETAC